Mechanical Recycling of PET Waste from Non-Woven Fabrics by Reactive Extrusion with Chain Extenders - Bimestre, Breno Heins; Saron, Clodoaldo (Journal of Research Updates in Polymer Science, 2014)
Mechanical recycling of poly (ethylene terephthalate) (PET) is an important industrial activity with direct effect for environmental saving. However, recycled PET (R-PET) undergoes progressive degradation during each recycling process, leading to considerable loss of properties such as mechanical, thermal and melting strength. Chain extenders have been successfully used to increase molecular weight of R-PET, improving process ability and mechanical performance of the material. The aims of this work was to evaluate the performance of the compounds polymeric methylene diphenyldiisocyanate (PMDI) and bis-(2,4-di-t-butylphenol) pentaerythritoldiphosphite (Irgafos®126) for potential use as chain extenders when compared to the traditional chain extender pyromelliticdianhydride (PMDA). Tensile testing, differential exploratory calorimetry, viscometry and dynamic rheometry were used to evaluate changes in mechanical properties, crystallinity, molecular weight and rheological properties of R-PET. PMDI showed effective action on increase in molecular weight and improvements in mechanical and rheological properties of R-PET, while Irgafos 126 causes depreciation of properties of the R-PET after initially to increase the molecular weight of the polymer. Thus, the use of PDMI as chain extension can represent an important alternative for mechanical recycling of highly degraded PET.